Hospitallers and Others. Military and Social Encounters. Edited by Christie Majoros, Maria Bonet Donato, and Julia Pavón Benito. : Crusades Subsidia. Abingdon–New York: Routledge, 2025. xi + 127 pp., ill. ISBN 978-1-032-61520-2. - Borchardt, Karl (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)